2019
DOI: 10.1101/584730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dot-compartment revealed? Diffusion MRI with ultra-strong gradients and spherical tensor encoding in the living human brain

Abstract: The so-called "dot-compartment" is conjectured in diffusion MRI to represent small spherical spaces, such as cell bodies, in which the diffusion is restricted in all directions. Previous investigations inferred its existence from data acquired with directional diffusion encoding which does not permit a straightforward separation of signals from 'sticks' (axons) and signals from 'dots'. Here we combine isotropic diffusion encoding with ultra-strong diffusion gradients (240 mT/m) to achieve high diffusionweighti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Obtaining indices of the neurite (or axonal) density may be possible, although their usefulness is limited to conditions where confounding factors are small or can be reliably constrained. One such condition could be healthy white matter, where the effects of T2 relaxation (Clark & Le Bihan, ; Tax et al, ) and isotropic heterogeneity (Dhital, Kellner, Reisert, & Kiselev, ; Szczepankiewicz et al, ) appear to be small, and where excellent (ex‐vivo) correlations have been demonstrated between the “stick” fraction and histological metrics of axonal density (Jespersen et al, ). Thus, in healthy white matter, existing methods such as WMTI (Fieremans, Jensen, & Helpern, ), NODDI or SMT may be able to capture the relative variation of axonal density.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obtaining indices of the neurite (or axonal) density may be possible, although their usefulness is limited to conditions where confounding factors are small or can be reliably constrained. One such condition could be healthy white matter, where the effects of T2 relaxation (Clark & Le Bihan, ; Tax et al, ) and isotropic heterogeneity (Dhital, Kellner, Reisert, & Kiselev, ; Szczepankiewicz et al, ) appear to be small, and where excellent (ex‐vivo) correlations have been demonstrated between the “stick” fraction and histological metrics of axonal density (Jespersen et al, ). Thus, in healthy white matter, existing methods such as WMTI (Fieremans, Jensen, & Helpern, ), NODDI or SMT may be able to capture the relative variation of axonal density.…”
Section: Discussionmentioning
confidence: 99%
“…Third, due to the SNR penalty from studying deep gray matter while using small voxels, we acquired multi‐echo data for a maximum b ‐value of 0.5 ms/μm 2 . Accordingly, we could only rely on a TE dependence of the mean diffusivity to separate compartment T2 values (Equation ), an effect that has previously been demonstrated to be small in the healthy brain (Clark & Le Bihan, ; Qin et al, ; Tax et al, ; Veraart, Novikov, & Fieremans, ). Acquiring multi‐echo data for higher b‐values may be a promising way forward (Veraart, Novikov, & Fieremans, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tensor‐valued encoding can probe features of the tissue microstructure that cannot be probed by conventional encoding alone (e.g., microscopic anisotropy, orientation coherence, and isotropic heterogeneity of tissue). It can also inform biophysical models . Waveforms that yield tensor‐valued encoding have been proposed in both symmetric and asymmetric variants .…”
Section: Introductionmentioning
confidence: 99%